Managing up and down: community corrections middle managers’ role conflict and ambiguity during organizational change - Kras, Kimberly R. (Journal of crime and justice, 2017)
Community corrections agencies in the United States must respond to and refine organizational practices depending on both internal (i.e. staff, resources, etc.) and external factors (i.e. political change, legislative action or union influence). Most prior studies emphasize the experiences of either upper management or line staff, but few studies focus on middle managers, who play a ‘strategic role’ in organizational reform. The current study explores the way(s) middle managers address policy implementation that often require reconcilement of conflict and ambiguity that often occur in translating policy to practice. The study uses ethnographic observations of and focus groups with 75 middle managers in a community corrections agency undergoing specialized training. Findings suggest middle managers resolve dissonance, and manage up, laterally and down, by employing three cognitive scripts: resignation, refocusing, and reinforcement. Each script presents distinct implications for organizational change processes and daily operations. Organizational reform creates deficits in middle managers’ role definition and more global impacts on their perception of organizational legitimacy within the agency’s goal framework. This work yields suggestions for future research and implications for mid-level managerial policy in corrections agencies.